A field study of vertical mobility and relative bioavailability of Cu and Ni in calcareous soil. Issue 1 (1st January 2020) - Zhao, Rui; Li, Jumei; Ma, Yibing; Lv, Yizhong
ABSTRACT: The vertical mobility of heavy metals in the soil profile may affect their bioavailability. In the present study, a field experiment was conducted for 11 years to investigate the vertical mobility of copper (Cu) and nickel (Ni) and the effects on their bioavailability in soil. It was found that the type and concentration of heavy metals are factors that affect mobility. After 11 years, the mobility and movement of Ni were greater than that of Cu from topsoil (0–20 cm) to subsoil (20–60 cm). The vertical mobility of Cu decreased with the increased addition of Cu, while Ni had the highest vertical mobility when its concentration was the highest in soil. The aging processes and vertical movement could lead to decreases in Cu availability (68–78%) and Ni availability (83–89%). For the decrease of Cu availability in soil, the main driving factor was the vertical movement at low added concentrations, but gradually became aging processes with the increase of added Cu concentrations, while Ni had the opposite tendency. Compared with Cu, aging and vertical mobility played a more prominent role in decreasing the bioavailability of Ni, the bioavailability of Cu changed less than that of Ni after 11 years. The decreased rate of Cu in wheat grains was about 0.26–1.05% while that of Ni was about 2.48–9.46% per year from 2009 to 2018. Therefore, the influence of the vertical downward movement of heavy metals should not be ignored in the assessment of the risk and bioavailability of heavy metals in soil.